ChemInform Abstract: Asymmetric Synthesis and Absolute Configuration of (+)‐ and (‐)‐Perhexiline. Issue 24 (27th May 2016) - Tseng, Chih‐Chung; Greig, Iain R.; Harrison, William T. A.; Zanda, Matteo
Abstract: A scalable, chiral auxiliary‐based asymmetric synthesis of (‐)‐(S)‐perhexiline (I) is developed which is applied to the preparation of the opposite enantiomer.